Luminescence Properties of InAlAs/AlGaAs Quantum Dots Grown by Modified Molecular Beam Epitaxy - 권세라; 류미이; 송진동 (한국진공학회, 2014)
Self-assembled InAlAs/AlGaAs quantum dots (QDs) on GaAs substrates were grown byusing modified molecular epitaxy beam in Stranski-Krastanov method. In order to study thestructural and optical properties of InAlAs/AlGaAs QDs, atomic force microscopy (AFM)and photoluminescence (PL) measurements are conducted. The size and uniformity of QDshave been observed from the AFM images. The average widths and heights of QDs areincreased as the deposition time increases. The PL spectra of QDs are composed of twopeaks. The PL spectra of QDs were analyzed by the excitation laser power- andtemperature-dependent PL, in which two PL peaks are attributed to two predominant sizesof QDs.